Short communicationMyocardial ischemia induced by three-vessel coronary-cameral fistulas - Oylumlu, Mustafa; Yildiz, Abdulkadir; Yuksel, Murat; Akyuz, Abdurrahman (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Coronary-cameral fistula is a scarce clinical entity, which is defined as an anomalous communication between any epicardial coronary artery and cardiac chambers or large vessels. We aimed to present a case of multiple coronary-cameral fistulas causing myocardial ischemia.